VD_FINDINFO HC / 2012 / 75 vom 18. Januar 2012 - VD Tribunal cantonal (2012)
MESURE PRÉPROVISIONNELLE, SUPPRESSIONEN GÉNÉRAL, MESURE PROVISIONNELLE | 263 CPC (CH), 308 al. 1 let. b CPC (CH), 314 al. 1 CPC (CH)